Uptake of Photosensitizer 2-Devinyl-2-(1-methoxylethyl) Chlorin f in Human Breast Cancer Cells: A Diffusion Kinetics Study - Ping Chen; Feng Zhang; Lei Zhang; Song-Cheng Mao; Lie Lin; Hua Bai; Guo-Qing Tang; Jian-Zhong Yao; Jun-Hong Yang; Yun-Feng Ma (International Journal of Photoenergy)
The kinetics of photosensitizer 2-devinyl-2-(1-methoxylethyl) chlorin f (CPD4) uptake in MCF-7 human breast cancer cells is described by a diffusion kinetics model and experimentally investigated using laser scanning confocal microscopy (LSCM). CPD4 permeated into MCF-7 cells with increasing incubation time, which was followed by its binding to cell organelles. Subcellular distribution study revealed that CPD4 was primarily localized on the mitochondria and membranes, supporting that the mode of transmembrane transport was diffusion. A kinetics model describing CPD4 passing through the plasma membrane of MCF-7 cells was proposed based on Fick's first law of diffusion. The kinetics of cellular uptake of CPD4 was studied by three-dimensional LSCM. By fitting the experimental data using the above model, important cellular uptake and distribution parameters were obtained, which are of clinical significance in photodynamic therapy.